2017
DOI: 10.1016/j.jpsychires.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Automated measurement of hippocampal subfields in PTSD: Evidence for smaller dentate gyrus volume

Abstract: Smaller hippocampal volume has been consistently observed as a biomarker of posttraumatic stress disorder (PTSD). However, less is known about individual volumes of the subfields composing the hippocampus such as the dentate gyrus and cornu ammonis (CA) fields 1-4 in PTSD. The aim of the present study was to examine the hypothesis that volume of the dentate gyrus, a region putatively involved in distinctive encoding of similar events, is smaller in individuals with PTSD versus trauma-exposed controls. Ninety-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 24 publications
0
89
5
Order By: Relevance
“…An estimation of statistical power for the largest published study (n=97) [7] to detect group differences in CA1 volume based on the effect size we observed (Cohen’s d=.21), reveals only 55.3% power to reject the null hypothesis or a 44.7% chance of a false positive. By comparison, the present sample size (n=282) based on the same effects size (0.21) attains 94.9% power to reject the null or a 5.1% chance of a false positive.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…An estimation of statistical power for the largest published study (n=97) [7] to detect group differences in CA1 volume based on the effect size we observed (Cohen’s d=.21), reveals only 55.3% power to reject the null hypothesis or a 44.7% chance of a false positive. By comparison, the present sample size (n=282) based on the same effects size (0.21) attains 94.9% power to reject the null or a 5.1% chance of a false positive.…”
Section: Discussionmentioning
confidence: 88%
“…No PTSD-associated differences in hippocampal shape were detected with vertex-based morphometry. Compared to previously published reports of hippocampal subfield volume in PTSD [7], our study used a sample size that was over 2.5 times larger and employed more advanced methods for segmentation of 12 hippocampal subfields based on an atlas constructed from ultra-high resolution MRI scans of postmortem brains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the insights that measures of eye movements can bring to diagnostics, the manner by which visual exploration occurs may provide therapeutic benefits for mental health disorders, such as depression, anxiety, and, in particular, PTSD, for which decreases in hippocampal subfield volume and altered patterns of hippocampal functional connectivity have been observed . Eye movement desensitization and reprocessing (EMDR) is a treatment technique in which emotional or traumatic memories are recalled (such as in the case of PTSD), while lateral saccades are made .…”
Section: Applications Of Research Linking Memory To Visual Explorationmentioning
confidence: 99%
“…Moreover, previous studies have demonstrated that stress‐related disorders and stress exposure are associated with reductions in the volume of the hippocampus in humans. For instance, cross‐sectional studies have shown that PTSD is related to reductions in hippocampal volume . Additionally, individuals with psychosocial trauma showed reduced hippocampal volume .…”
Section: Discussionmentioning
confidence: 99%